Phytotoxic potential of aqueous leaf extract of Tocoyena formosa and Rudgea viburnoides - Hilares Vargas, Sharmely; Barbosa Coelho, Maria de Fátima; Simon Cowo, Elbert; Murga Orrillo, Hipolito; Spiller, Carla (Revista Ceres, 2025)
Plants have organic components produced as secondary metabolites able to positively or negatively interfere on normal development of other species. The objective of this research was to determine the phytotoxic effects of aqueous leaf extract from two species Rubiaceae family: Tocoyena formosa and Rudgea viburnoides on the germination and initial development of lettuce (Lactuca sativa L). The extract was obtained from mixing 50 g of fresh leaf and 500 mL of distilled water. The experiment was arranged in completely randomized design for each specie, subjected to five extract concentrations: 0, 25, 50, 75 and 100%; and 4 repetitions of 50 seed each. The bioassays were performed in laboratory at controlled temperature and luminosity during seven days. Results showed that the aqueous extract of both species do not affected the germination and the percent of abnormal lettuce seedlings. R. viburnoides showed no pronounced difference in relation to shoot length and dry biomass; however, the root length was reduced by 85%. The extract of T. formosa at higher concentrations, drastically reduce the dry biomass and length of shoots and roots. Therefore, both species have phytotoxic effect on seedling growth of lettuce being the length root the most affected variable.